Pengaruh Harga Diskon Dan Kualitas Produk Terhadap Keputusan Pembelian Online (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2024)
This study aims to analyze the effect of discount pricing and product quality on online purchasing decisions. A quantitative method with multiple regression analysis was employed. Data were collected through questionnaires from 45 respondents who had made online purchases. Based on the regression test results, the coefficient for discount pricing (x1) is 0.178 with a significance value of 0.079, indicating that discount pricing does not significantly influence online purchasing decisions. On the other hand, product quality (x2) shows a coefficient of 0.512 with a significance of 0.001, indicating a significant and positive impact on online purchasing decisions. The ANOVA test reveals that the regression model is significant overall, with an F value of 47.816 and a significance of 0.000. The conclusion of this study is that product quality has a greater and more significant influence compared to discount pricing on online purchasing decisions.